Insights into the E2F target genes in breast cancer: associations of pathway genes with prognosis and immune cell filtration based on in silico and ex vivo analyses - Behnoosh Nikonezhad; Maryam Lotfian; Nadia Manavi; Atefeh Zamani; Mohammad Mahdevar (Cancer Cell International)
Abstract Background E2F transcription factors are crucial in various biological processes, including cell proliferation, differentiation, and apoptosis. However, the exact role of E2F target genes in breast cancer (BC), as well as their influence on survival and immune response, remains poorly understood. Methods To investigate the differential expression of E2F target genes and their relationship with patient prognosis and immune cell infiltration, transcriptomic data from the Cancer Genome Atlas database were analyzed. A risk model was developed to identify genes associated with survival. BC samples were clustered into high-expression (C1) and low-expression (C2) groups of E2F target genes. The correlation between gene expression and factors such as survival, immune cell infiltration (CD4 + and CD8 + T cells), and immune checkpoint inhibitors (PD-L1 and PD-L2) was analyzed. We analyzed the link between clusters and clinical characteristics using the chi-squared test. For further investigation, single-cell data from GSE243526 were utilized. For validation, the expression levels of JPT1 and TBRG4 were assessed using RT-qPCR in clinical samples. Results Genes targeting E2F, such as AURKB, JPT1, TBRG4, and KIF4A, showed increased expression linked to poor patient prognosis, regardless of clinical features. Kaplan-Meier survival analysis revealed that elevated expression of these genes correlated significantly with decreased survival rates and heightened mortality risk. Single-cell data confirmed that candidate genes exhibited higher expression in tumor-associated epithelial cells than healthy ones. Furthermore, samples from group C1 exhibited a lower survival rate than C2. Immune cell infiltration analysis determined that high expression of E2F target genes in the C1 subgroup was associated with diminished T cell infiltration and increased PD-L1 and PD-L2 expression. A strong and significant association was also identified between triple-negative breast cancer and the C1 cluster. RT-qPCR validation confirmed a significant elevation of JPT1 and TBRG4 expression levels relative to adjacent healthy tissues in BC. Conclusion These findings suggest that E2F target genes, including JPT1 and TBRG4, may act as prognostic biomarkers and contribute to immune evasion in BC. E2F target genes can also offer good potential for classifying and treating patients.